Pengaruh Pertumbuhan Penduduk, Pengangguran dan Pendidikan Terhadap Tingkat Kemiskinan Di Provinsi Kalimantan Selatan Tahun 2011-2020 - Paridah, Siti; Pahlevi, Khairi (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2023)
This study aims to determine the effect of population growth, unemployment, and education on poverty levels in South Kalimantan Province in 2011-2020. This type of quantitative research uses time series data for ten years using multiple linear regression analysis methods. The results showed that population growth, unemployment, and education significantly affected poverty simultaneously. Unemployment and education variables have a considerable effect partially; population growth variables do not affect the poverty level; the unemployment variable is the most dominant factor affecting the poverty level.